Increasing the length of an estradiol with progesterone timed artificial insemination protocol with 2 controlled internal drug release devices improves pregnancy per artificial insemination in lactating dairy cows - Pereira, M. H.C. [UNESP]; Lopes, F. R. [UNESP]; Munhoz, A. K. [UNESP]; Pohler, K. G.; Filho, R. V.O.; Cappellozza, B. I.; Vasconcelos, J. L.M. [UNESP] (American Dairy Science Association, 2021)
The objective of this study was to compare the effects of different lengths of ovulation synchronization protocols using 2 controlled internal drug release (CIDR) devices on ovarian dynamics and pregnancy outcomes in lactating dairy cows. Lactating Holstein cows (n = 1,979) were randomly assigned to receive timed artificial insemination (TAI; d 0) following 1 of 2 treatments: (1) 9-d protocol (n = 988; 9D) with 2 intravaginal devices containing 1.9 g of progesterone (CIDR) and 2.0 mg of estradiol benzoate on day −11; 25 mg (i.m.) of dinoprost tromethamine (PG) and withdrawal of 1 CIDR on d −4; 1.0 mg (i.m.) of estradiol cypionate, second CIDR withdrawal, and PG on d −2; and TAI on d 0 and (2) 10-d protocol (n = 991; 10D) with 2 CIDR and 2.0 mg of estradiol benzoate on d −12; 25 mg of PG and withdrawal of 1 CIDR on d −4; 1.0 mg of estradiol, second CIDR withdrawal, and PG on d −2; and TAI on d 0. There was no effect of protocol on estrus detection, whereas a greater percentage of cows from 10D had ovulated close to TAI [no corpus luteum (CL) at AI and a CL at d 7] versus cows assigned to 9D protocol. A protocol × heat stress (average cow temperature ≥39.1°C on day of AI and d 7) interaction was observed in a manner that pregnancy per AI (P/AI) was greater in non-heat-stressed 10D versus 9D cows, whereas P/AI did not differ when cows were under heat stress. Furthermore, 10D protocol did not increase P/AI when all cows that received AI were included in the analysis or in cows that ovulated near TAI. However, animals assigned to 9D without any event of heat stress had a reduced P/AI when compared with cows assigned to 10D without heat stress. A protocol × CL presence at the beginning of the protocol interaction was observed and cows with a CL at the beginning of the protocol had a greater P/AI in 10D versus 9D; meanwhile, in cows without a CL, no differences on P/AI were observed. The protocol × CL presence at the beginning of the protocol interaction on P/AI was also observed for cows that ovulated near TAI. A greater percentage of cows assigned to 9D had follicles of medium size (13–15.9 mm), and greater percentage of cows assigned to 10D had larger follicles (>16 mm). Increasing the length of an estradiol with progesterone–based ovulation synchronization protocol (10D vs. 9D) increased the proportion of cows with larger follicles (>16 mm) and increased P/AI in cows without heat stress and in cows with a CL at beginning of the protocol. Moreover, the 10D protocol increased the proportion of cows with ovulation near TAI, demonstrating the effectiveness of this protocol in improving the reproductive performance of lactating Holstein cows.
Keywords: artificial insemination; dairy cows; fertility; synchronization